EFEKTIVITAS LIMBAH TEMBAKAU TERHADAP WERENG COKLAT DAN PENGARUHNYA TERHADAP LABA-LABA PREDATOR - Tuti, Harlina Kusuma; Wijayanti, Retno; Supriyadi, Supriyadi (Universitas Sebelas Maret, 2014)
Nilaparvata lugens Stal.is one of plant pest which damages rice field. The waste of tobacco contains nicotine which can use as botanical insecticide. This research was aimed to find out the effectiveness of tobacco waste in controlling brown planthopper and its effect then predator (Oxyopes javanus). The methode of this research applies Completed Randomized Design experiment. In this research, used the kind of tobacco waste and various concentration with triple repeating. The variables of this research were mortality and death period of brown planthopper, mortality and eating capability of O. javanus viewed from direct and indirect application. The concentration 12,5% of tobacco roots extract cause mortality of brown planthopper reaches 93%. Furthermore, the concentration 12,5% of tobacco root extracts made the death period of brown planthopper faster than the other concentrations. Direct application of tobacco waste extracts did not cause of O. javanus. Indirect application of tobacco waste extract did not cause of death toward O. javanus, but caused eating capability of O .javanus. Extract from tobacco bark with concentration 3,125% dan 1,56% had the power repellent which was shown by O. javanus only eat 2,33 brown planthoppers per week.